Dental care in a patient with rare syndrome - huntington's disease. Case report - Cancado Figueiredo, Marcia (2021)
Huntington's disease (HD) is a rare neurodegenerative pathology that develops progressive dementias, involuntary, repetitive and random movements (chorea), which prevent the maintenance of oral health and dental approach. This paper reports management behaviors, professional adaptation and routine dental treatment during the follow-up for several years of a patient diagnosed with HD, who since 2015 has been treated in an outpatient clinic for patients with special needs where he sought dental treatment due to the caregiver's difficulty in maintaining oral health. Poor oral hygiene was diagnosed, causing plaque and calculus accumulation, multiple caries and partial edentulism. The aim of the treatment plan was to maintain the natural dentition and prevention based on the education of its caregiver. During the first 4 years, restorations and extractions were monitored and in the last years, supragingival scraping and polishing were performed, with preventive educational reinforcement for their caregivers. In the success of the treatment, it was important to prevent and prepare the dentist to welcome the patient with HD for care at the right place and at the right time, patience, clinical interest, the professional complicity of the entire team and the education associated with motivation of the caregiver, enabling the treatment of oral diseases and the promotion of the patient's quality of life, through a humanized clinical conduct.